The Natural Products and Extracts: Anti‐Triple‐Negative Breast Cancer in Vitro. Issue 7 (4th June 2021) - Chen, Han; Yang, Jiaping; Yang, Yanlong; Zhang, Jianpeng; Xu, Yao; Lu, Xiaoling
Abstract: Triple‐negative breast cancer (TNBC) makes up 15 % to 20 % of all breast cancer (BC) cases, and represents one of the most challenging malignancies to treat. For many years, chemotherapy has been the main treatment option for TNBC. Natural products isolated from marine organisms and terrestrial organisms with great structural diversity and high biochemical specificity form a compound library for the assessment and discovery of new drugs. In this review, we mainly focused on natural compounds and extracts (from marine and terrestrial environments) with strong anti‐TNBC activities (IC50 <100 μM) and their possible mechanisms reported in the past six years (2015–2021). Abstract :